BIOCHEMICAL AND TOXICOLOGICAL EFFECTS OF GLOBIMETULA BRAUNII (LORANTHACEAE) LEAF - Fred-Jaiyesimi, A.; Onabanjo, T.; Jaiyesimi, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Globimetula braunii (Engle) Van Tiegh, growing on the Cola acuminata tree is used in Nigerian traditional medicine as a laxative, against diabetes, as an antihypertensive and as an antimicrobial agent. Information on biological activity of this plant is scanty, however previous studies have reported the antidiabetic (Olagunju et al., 1999)) and laxative effects (Fred-Jaiyesimi et al., 2008) of the leaf. This study aims at investigating the biochemistry and safety of the ethanol extract of Globimetula braunii leaf by determining its pharmaco-toxicological effects after administration in rats. After administering the extract to rats for 14 days, no deaths occurred. A single daily oral administration of G. braunii ethanol extract (2 g/kg) significantly (p<0.05) lowered the triglyceride and cholesterol levels of the rats. A significant 22.2% and 58.7% reduction in the triglyceride level of the rats was observed on day 7 and 10 respectively while the blood cholesterol was lowered by 8.9% and 39.1%. The ethanol leaf extract had no effect however on the Packed Cell Volume of the animals. The histopathology results showed no morphological alterations in the brains, kidneys, hearts, small intestines and spleens of the animals that got the leaf extract administered. The livers were normal without lesions but showed mild mononuclear cell aggregation. This study indicates that G. braunii is non-toxic when administered acutely. It may also be helpful in managing and controlling complications such as atherosclerosis, cholesterolemia, cardiovascular diseases often associated with diabetes as well as hypertension. Further studies to evaluate these potentials are required. References: 1. Olagunju JA; Ismail FI; Gbile ZO (1999). The hypoglycaemic property of normal saline leaf extract of Globimetula braunii in alloxanized diabetic albino rats. Biomed. Lett. 60 (235): 83-89. 2. Fred-Jaiyesimi Adediwura, Onabanjo Temitope and Ademuyiwa Oluwakemi (2008). Phytochemical and laxative studies of Globimetula braunii (Engle) van Tiegh growing on Cola acuminata (Schott & Endl). AJTCAM (In press).